The Influence of Marketing Mix on Rocket Chicken Purchase Decisions Among Yogyakarta Students - Muhammad Salman Alfarizi; Moh Azzam Fachruddin; Muhammad Ilhan Mansis; Adyatma Pradipta Thama (MJK PUBLISHER, 2024)
Yogyakarta offers a wide variety of fast-food options, with numerous fast-food restaurants located throughout the city. This study focuses on the influence of the marketing mix on purchasing decisions at Rocket Chicken among University students in Yogyakarta. The research adopts a quantitative approach, utilizing questionnaires distributed to students from various universities in the region. The Sampling technique is Purposive Sampling, targeting 100 respondents determined using the Lemeshow formula. Data analysis methods include classical assumption tests, simple linear regression analysis methods include classical assumption tests, simple linear regression analysis, and hypothesis testing. The simple linear regression analysis resulted in the equation Y= 5.567 + 0.768X. The coefficient of determination indicates that 60.9% of purchasing decisions are explained by the variables studied, while the remaining percentage is influenced by factors outside the scope of this research. The T-test results demonstrate that the Marketing Mix (X) significantly impacts Purchasing Decisions (Y) (0.000<0,050)